HUBUNGAN ANTARA KEMAMPUAN BERPIKIR FORMAL DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN KIMIA KELAS XI IPA SMA NEGERI 1 SANGGAU - Erjayantri Nurul Rizki; Cawang Cawang; Rizmahardian Azhari Kurniawan (Universitas Muhammadiyah Pontianak, 2016)
ABSTRACT Chemistry is characterized by abstract concepts and theories which is rather difficult and requires formal thinking skill. This research was aimed to describe student’s formal thinking skill, student’s learning achievement, and the correlation between of them. Students of XI IPA were used as population of this research, while 29 students from XI IPA 1 were chosen as samples. The sampling used purposive sampling technichuques. Student’s formal thinking skill data were collected using Test of Logical Thinking (Tobin and Capie, 1981). The results showed that 72,41% students were in formal thinking stage, while 24,14%, and 3,45% students were in transitional stage and concrete stage, respectively. Student’s learning achievement data were analyzed from student’s semester test and it was found that student average score was 70,86. Correlation between student’s formal thinking and student’s learning achievment was analyzed using pearson product moment. It was concluded that ‘formal thinking ability’ affected student achievement by 0,527 in coefficient correlation, and 0,2774 in coefficient determination.Keywords: learning results, formal thinking skill, chemistry learning, Test of Logical Thinking